DEVELOPING THE SRIRITUAL-AESTHETIC AND PATRIOTIC SPIRIT OF STUDENTS IN HIGHER EDUCATION INSTITUTIONS - Otaboboyeva Umida Ilhomovna (Bright Mind Publishing, 2025)
This article discusses spiritual and educational development; social and didactic development; philosophical and pedagogical development; obedience to national moral norms; scientific education; purity of views and clarity of thinking; respect for national principles; patriotism, goodwill, feelings of justice; selflessness, courage, courage, initiative; readiness to defend the independence of the country and people and serve them.